Becoming a Reflective Planning Educator. Issue 4 (1st October 2016) - Wachs, Martin
Abstract : After a 45-year career as a professor and practitioner of planning, the author reflects on relationships among research, professional practice, and teaching. While his efforts to directly influence public policy through practice often met with limited success at the time, he finds that practice greatly enriched his teaching and his work did eventually influence practice, primarily through the professional work of his students. Because of changing academic culture, junior planning faculty today have far less opportunity to engage in practice than in the past. The education of practitioners is challenged by the growing absence of senior faculty whose research is influenced by practice.